Kajian Rancang Bangun Aplikasi Praktikum Mata Kuliah NOTAM Program Studi Manajemen Lalu Lintas Udara - Ida Umboro Wahyu Nur Wening; Bayu Purbo Wartoyo; Aprinia Kusumaningsih (Politeknik Penerbangan Makassar, 2022)
The changes in the curriculum and syllabus of the Air Traffic Management study program became the background of the research. Updating learning media is expected to be able to support the learning process. The purpose of the study was to determine practical learning and the urgency of learning media needs for the NOTAM course practicum. The type of research used in this research is descriptive quantitative and qualitative research with survey methods. Students stated that the current practical learning of NOTAM courses out of ten indicators had positive scores with scores above 92%. Based on the questionnaire results, 100% of respondents agree that the urgency of the current practicum learning media is very much needed. The research was reinforced by the interview results with the supervisor, who stated that the success rate of participants in the practicum was around 70% and suggested practicum learning media so that students could demonstrate the making of NOTAM.